2008
DOI: 10.1177/0886260508325496
|View full text |Cite
|
Sign up to set email alerts
|

Gender Symmetry, Sexism, and Intimate Partner Violence

Abstract: The current study of a diverse sample of 92 male and 140 female college students has two goals: to make an empirical contribution to the debate regarding gender symmetry in intimate partner violence with data from both males and females; and to address inconsistent findings in studies examining the relationship between sexist attitudes and intimate partner violence (IPV; in which some studies find a positive relationship between men's sexism and their IPV, while other studies find protective effects of sexism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
3
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 42 publications
15
138
3
22
Order By: Relevance
“…Although this finding might challenge, research showing that more sexist, misogynistic, traditional, and gender rigid attitudes are related to IPV against women (Allen, Swan, & Raghavan, 2009;Flood & Pease, 2009), empirical research on male batterers have consistently found that antisocial/generally violent batterers show the highest levels of hostility toward women Holtwortz-Munroe & Stewart, 1994). Also, evidence from general population studies indicates that more violent individuals might also hold hostile attitudes toward women ) as compared to less violent individuals.…”
Section: Discussionmentioning
confidence: 83%
“…Although this finding might challenge, research showing that more sexist, misogynistic, traditional, and gender rigid attitudes are related to IPV against women (Allen, Swan, & Raghavan, 2009;Flood & Pease, 2009), empirical research on male batterers have consistently found that antisocial/generally violent batterers show the highest levels of hostility toward women Holtwortz-Munroe & Stewart, 1994). Also, evidence from general population studies indicates that more violent individuals might also hold hostile attitudes toward women ) as compared to less violent individuals.…”
Section: Discussionmentioning
confidence: 83%
“…La quinta hipótesis establecía que la violencia es reactiva en ambos sexos o solo en hombres, mientras que la victimización y perpetración son independientes en mujeres, considerándose que modelos de violencia cruzada o proactiva tendrían peor ajuste, siendo este último más plausible en hombres, tal como hallaron Allen et al (2009) en su estudio. Como se esperaba, se encontró una correlación entre victimización y perpetración en ambos sexos (Allen et al, 2009;Moral de la Rubia & López Rosales, 2012, 2014, siendo muy alta en hombres; en cambio, fue baja y mediada por el ajuste diádico en mujeres.…”
Section: Discussionunclassified
“…Oxtoby (2012) halló independencia entre victimización y perpetración en mujeres estudiantes universitarias mexicanas, señalando su dificultad para concebirse a sí mismas como agentes de violencia en una cultura latina que las percibe como víctimas. Es importante remarcar que los estudios de Moral de la Rubia y López Rosales (2012Rosales ( , 2014, Allen et al (2009) y Oxtoby (2012 se basan en datos de autorreporte que consideran únicamente la perspectiva del respondiente. Esta perspectiva podría motivar que las respuestas a los cuestionarios fueran más concordantes con modelos de violencia reactiva y de desconexión entre victimización y perpetración que con modelos de violencia proactiva y cruzada, ante valores e identidades de rechazo de la violencia.…”
unclassified
“…Benevolent sexism, however, is a less obvious form of sexism and is based on general attitudes toward women as filling traditional gender roles and stereotypes (Allen, Swan, & Raghavan, 2009). Ambivalence occurs as one attempts to rationalize both forms of sexism frequently faced in everyday life.…”
Section: Ambivalent Sexismmentioning
confidence: 99%